2022
DOI: 10.1227/ons.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Single-Center Experience Using a 3D4K Digital Operating Scope System for Aneurysm Surgery

Abstract: BACKGROUND: In recent years, 3D4K exoscope systems (EXs) have been introduced to microneurosurgery and reported to be an alternative to conventional operating microscopes (OMs). This study reviews our single-center experience using an 3D4K EX in intracranial aneurysm surgery. OBJECTIVE: To investigate the applicability of a novel 3D4K EX for intracranial aneurysm surgery. METHODS: A retrospective analysis of patients who underwent microsurgical repair of incidentally or ruptured cerebral aneurysms between Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There was no statistical difference regarding duration of surgery, aneurysm occlusion rates, or surgical complication rates including intraoperative rupture. 12 Although Pantel et al 12 found success with the exoscope in aneurysm surgery, there are neurosurgical procedures where the exoscope may not be equivalent to incumbent optical systems. 6 Surgeries performed through a narrow corridor such as through a small corticectomy or transsphenoidal pituitary surgery has been reported to be difficult to perform with the exoscope because of the operator's hand blocking the view or the light source.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There was no statistical difference regarding duration of surgery, aneurysm occlusion rates, or surgical complication rates including intraoperative rupture. 12 Although Pantel et al 12 found success with the exoscope in aneurysm surgery, there are neurosurgical procedures where the exoscope may not be equivalent to incumbent optical systems. 6 Surgeries performed through a narrow corridor such as through a small corticectomy or transsphenoidal pituitary surgery has been reported to be difficult to perform with the exoscope because of the operator's hand blocking the view or the light source.…”
mentioning
confidence: 99%
“…There was no statistical difference regarding duration of surgery, aneurysm occlusion rates, or surgical complication rates including intraoperative rupture. 12…”
mentioning
confidence: 99%
See 1 more Smart Citation